Are three languages better than two? inhibitory control in trilinguals and bilinguals in the Philippines - Madrazo, Arnel R.; Bernardo, Allan B.I (Philippine Journal of Psychology, 2012)
"This study tests the hypothesis that there is no difference between bilinguals and trilinguals due to similar cognitive processes involved in suppressing information from irrelevant languages, regardless of the number of irrelevant languages."